(untitled) (Herald of the National Children’s Medical Center, 2022)
Down syndrome is the most common chromosomal pathology. It occurs when, as a result of a random mutation, another chromosome appears in the 21st pair. Often, children with Down syndrome (DS) and related disorders have a lower IQ level, severe forms of stereotypical behavior. Aim: to study neurological conditions in children with DM. Conducting clinical neurological, neurophysiological and audiological studies in 34 children (16 boys, 18 girls) with DM. The Stanford-Binet scale was used to determine the intellectual status of children with DM. The manifestation of autistic disorders, somatic pathology, lack of speech activity are unfavorable prognostic factors in children with DM.